Bad Boys Meet the Swan of Avon: A Re-Visioning of Hamlet in Sons of Anarchy - Burzyńska, Katarzyna (Studia Anglica Posnaniensia, 2017)
This article investigates the intersections between Shakespeare’s Hamlet and a popular TV series Sons of Anarchy (SOA), loosely based on the Shakespearean original. The crime drama series revolves around an outlaw motorcycle club that literally “rules” a fictional town in California like an old royal family with its own brutal dynastic power squabbles and dark family secrets. The club is governed by an unscrupulous President Clay and an equally violent, though more conflicted, Vice President Jax Teller, the son of the late President, who had died in mysterious circumstances. In the article I argue that the popularity of the series lies not in its graphic scenes of violence, over-the-top Harley chases, and sex intrigues, but rather in its Shakespearean and Renaissance structure. SOA, dubbed as “Hamlet on Harleys”1, is an appropriation rather than an adaptation of Shakespeare’s tragedy, which makes it a truly transmedial phenomenon. The article investigates a fascinating blend of seemingly marginal elements of modern American culture and the canonical British tragedy. It also addresses the connections between the lifestyles of the so called outlaw MC clubs and the early modern family structure as presented in Hamlet, focusing on the issues of power and gender relations.